2018
DOI: 10.1007/s10792-018-0940-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultra-wide-field fundus ophthalmoscopy-assisted deep learning, a machine-learning technology, for detecting age-related macular degeneration

Abstract: A combination of DCNN with Optos images is not better than a medical examination; however, it can identify exudative AMD with a high level of accuracy. Our system is considered useful for screening and telemedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…There are studies in the ophthalmology literature on the use of fundus cameras and the suitability of the automatic diagnosis of retinal diseases. 58 Matsuba et al 59 reported in their study that patients with AMD could be detected with high sensitivity using deep learning and Optos imaging, without ophthalmological examination.…”
Section: Use Of Fundus Autofluorescence In Geographic Atrophymentioning
confidence: 99%
“…There are studies in the ophthalmology literature on the use of fundus cameras and the suitability of the automatic diagnosis of retinal diseases. 58 Matsuba et al 59 reported in their study that patients with AMD could be detected with high sensitivity using deep learning and Optos imaging, without ophthalmological examination.…”
Section: Use Of Fundus Autofluorescence In Geographic Atrophymentioning
confidence: 99%
“…We use Gradient-weighted Class Activation Mapping (GradCAM) [14] to generate image-and label-wise explanations because it is a well-established method (e.g. [18,19,20]) and because it is generally faithful to how the explained model works. Other methods have been shown to be akin to simple edge detectors and to yield very similar heatmaps even when replacing the trained model weights with random weights [21,22].…”
Section: Image-wise Explanationsmentioning
confidence: 99%
“…It has been shown that artificial intelligence can be used to develop algorithms that automatically detect retinal diseases, for example, AMD and DR. 32 The first algorithm to classify severity of DR received Federal Drug Administration (FDA) approval in the USA in 2018. 33 Tools for automatic OCT pattern recognition and referral decision-making have already been published and could be integrated into a cloud-based referral platform.…”
Section: Future Applications and Economic Impactmentioning
confidence: 99%